The Influence of Mind Mapping and Learning Motivation towards Reading Comprehension on Recount Text of the Eighth Grade Students of Junior High School 11 Palembang - Elin Sustia Sari; Baginda Simaibang; Mulyadi Mulyadi (ELTE Journal (English Languange Teaching and Education), 2018)
AbstractThis study was meant to reveal the influence of mind mapping strategy and learning motivation towards reading comprehension on recount text of the eighth grade students of Junior High School 11 of Palembang. In this study 60 students of eighth grade students of Junior High School 11 in the academic year 2017/2018 were chosen as samples by means of two stage random sampling. This study applied factorial research design. The data were collected by using questionnaire and test. The data were analyzed by using Paired Sample t-test, Independent Sample test, and Two-WayANOVA. The results showed that, first, there was a significant difference in students’ reading comprehension taught using mind mapping strategy. Second, there was not any significant difference in students’ reading comprehension taught by traditional teaching method. Third, there was significant difference in students’ readingcomprehension students who had high and low learning motivation by using mind mapping strategy and traditional teaching method. Fourth, there were not any significant interaction effects of mind mapping strategy and learning motivation towards the students’ reading comprehension of Junior High School 11 of Palembang.Conclusion suggests that there were significant influences of mind mapping strategy and learning motivation towards reading comprehension on recount text of the eighth grade students of Junior High School 11 of Palembang. In line with, mind mapping strategy was effective to the students who have high and low learning motivation.Keywords: Mind Mapping Strategy, Traditional Teaching Method, Learning Motivation, Reading Comprehension.